The burden of cancer in Belgium, 2004-2017. (30th September 2020) - Cornez, A; Silversmit, G; Gorasso, V; Grant, I; Wyper, G M A; De Smedt, D; Devleesschauwer, B; Speybroeck, N
Abstract: Background: Monitoring the health status of a population requires consistent and comparable data on the morbidity and mortality impacts of a disease. The Disability-Adjusted Life Year (DALY) is an increasingly used disease burden indicator, combining healthy life years lost due to living with disease (Years Lived with Disability; YLDs) and due to dying prematurely (Years of Life Lost; YLLs). In Belgium, as in many other developed countries, cancer is a major contributor to the overall burden of disease. To date, however, local estimates of the burden of cancer are lacking. Methods: We estimated the burden of 48 cancers in Belgium from 2004 to 2017 in terms of DALYs, using national population-based cancer registry data and international disease models. We developed a microsimulation model to translate incidence- into prevalence-based estimates, and used expert elicitation to integrate the long-term impact of surgical treatment. Results: In 2017, in Belgium, breast cancer was the cancer with the highest disease burden among women, followed by lung cancer and colorectal cancer. Among men, lung cancer had the highest disease burden, followed by colorectal cancer and prostate cancer. Between 2004 and 2017, the burden of lung cancer increased by more than 50% in women, while in both sexes, significant increases were observed in melanoma and skin cancer burden. The majority of the cancer burden remained linked to premature mortality. Conclusions: Cancer maintains a major impact on the health of the Belgian population. Current resources allocated for their prevention and treatment will need to be maintained to further reduce the cancer burden. Lung cancer remains a crucial challenge, among both men and women, calling for strengthened tobacco control policies. Integrating the current study in the Belgian national burden of disease study (BeBOD) will allow monitoring the burden of cancer over time, highlighting new trends and assessing the impact of public health policies. Key messages: Burden of disease studies allow assessing and monitoring the impact of diseases and risk factors in a comparable way. Cancer maintains a major impact on the health of the Belgian population; lung cancer in particular remains a crucial challenge.